Dampak Kebijakan Moneter Terhadap Hukum Perbankan: Analisis dan Implikasi Studi Pada Dampak Pandemi COVID-19 Terhadap Pasar Keuangan Indonesia - Son Junior Estomihi; Daniel Darel Amadeo; Andrew Samuel Pandiangan (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The COVID-19 pandemic has had a significant impact on the global economy, including Indonesia, by facing major challenges in financial markets and monetary policy. This study explores how this crisis has affected five major financial markets in Indonesia: the Rupiah (IDR) interbank money market, the US Dollar (USD) interbank money market, the government bond (SUN) market, the stock market, and the USD/IDR spot market. The method used is desk research that collects data from various relevant literature sources. The results of the study show that interest rate policy has a significant impact on the IDR and USD interbank money markets, while the IDR minimum GWM ratio affects medium-term SUN yields and the stock market sector index. However, the impact of BI's market operations is mostly insignificant. In addition, certain policy measures show an increased impact during the pandemic, especially in the IDR and SUN interbank money markets. This study recommends that the central bank implement a more expansionary monetary policy and consider market behavior that is responsive to pandemic news. A combination of alternative monetary strategies and fiscal actions can improve post-pandemic economic stability